2019
DOI: 10.18632/oncotarget.27027
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of novel and complementary targets for immunotherapy: an analysis of gene expression in the tumor microenvironment

Abstract: Background: Immunotherapies targeting immune checkpoint proteins CTLA-4, PD-1, and PD-L1 have saved lives, but these therapies have only been effective in some patients. Patients positive for expression of immune checkpoint proteins in the tumor microenvironment show better response to immune checkpoint inhibitors. Consequently, knowledge of which genes are consistently expressed in lymphocytes within the tumor microenvironment can convey potentially effective and complementary new immunotherapy tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Despite the potential responses with long overall survival, but response rate still remains limited (less than 20%) (Franklin et al 2017 ). Several factors are closely related to the response of ICBs including immune phenotype, target gene expression and tumor mutation burden (Gaffney et al 2019 ; Gao et al 2016 ; Zaretsky et al 2016 ). Another important factor is loss of functions in the antigen processing and presentation, which governs generation, recognition, binding and presentation to the cell surface.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential responses with long overall survival, but response rate still remains limited (less than 20%) (Franklin et al 2017 ). Several factors are closely related to the response of ICBs including immune phenotype, target gene expression and tumor mutation burden (Gaffney et al 2019 ; Gao et al 2016 ; Zaretsky et al 2016 ). Another important factor is loss of functions in the antigen processing and presentation, which governs generation, recognition, binding and presentation to the cell surface.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients with a high correlation of CD3E-PD-1 did not respond, while other patients with low correlation did respond to anti-PD-1 treatment. When examining anti-PD-1 responders and nonresponders in metastatic melanoma, scholars found a significantly higher correlation between CD3E and PD-1 between responders and nonresponders, which supports the tumor hypothesis related to CD3E expression in the microenvironment [28]. That can be used as a useful criterion for identifying new therapeutic targets with potential for therapeutic response.…”
Section: Discussionmentioning
confidence: 55%
“…Hart et al has reported that a reduced cell surface abundance of CD3E could lead to a significant inhibition of T cell killing capacity ( Hart et al, 2019 ). In contrast, the increased expression of CD3E was found markedly related to the effective response in 31 cancer types patients who received anti-PD1 immunotherapy ( Gaffney et al, 2019 ). CD3D has been reported as a potential biomarker for the response to ICIs and prognosis in cancers, including colon cancer and muscle-invasive bladder cancer ( Klintman et al, 2016 ; Shi et al, 2019 ; Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%